1998
DOI: 10.1002/ctpp.2150380305
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Atmospheric Pressure Glow Discharge

Abstract: The atmospheric pressure glow discharge (APGD) is a new type of the discharge discovered by OKAZAKI et al.[l] recently. The APGD can be used in practical application (e.g. ozone generation), but the phenomena occurring in the discharge are not fully understood. We studied the APGD driven at 50 Hz, applied voltage up to 5 kV and burning in helium, argon and nitrogen. We used a planar configuration of discharge cell:electrode. Between the metal electrode and the dielectric plate a fine metal mesh was placed. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 9 publications
1
38
0
Order By: Relevance
“…With additives or a special sandwich structure placing a wire mesh between the dielectric and the metal electrode also in air, O 2 and Ar stable glows were obtained in atmospheric pressure DBDs, even when using a 50 Hz source [34]. These experiments were repeated and confirmed by many groups [35]. The function of the wire mesh at the back side of the dielectric remained a mystery for a long time.…”
Section: Diffuse Volume Barrier Dischargesmentioning
confidence: 80%
See 1 more Smart Citation
“…With additives or a special sandwich structure placing a wire mesh between the dielectric and the metal electrode also in air, O 2 and Ar stable glows were obtained in atmospheric pressure DBDs, even when using a 50 Hz source [34]. These experiments were repeated and confirmed by many groups [35]. The function of the wire mesh at the back side of the dielectric remained a mystery for a long time.…”
Section: Diffuse Volume Barrier Dischargesmentioning
confidence: 80%
“…The function of the wire mesh at the back side of the dielectric remained a mystery for a long time. Through the work of Tepper [36] and that of Fang [35] it was clarified that the mesh initiates a corona discharge that evenly charges the PET (polyethyleneterephthalate) dielectric, which is an electret material. When a certain threshold voltage is reached charge carriers are spontaneously expelled into the main gas gap (polarization switching).…”
Section: Diffuse Volume Barrier Dischargesmentioning
confidence: 99%
“…For the discharges operating in air and nitrogen, a large number of spike-like current pulses with nanosecond duration randomly appear at every half cycle of the applied voltage, which is typical for a DBD operating in the filamentary mode [25,27,34]. In contrast, for the argon and helium discharges, one single current pulse with durations up to a few ls appear at every half cycle of the applied voltage, which means that these discharges operate in the glow mode [32,34,35]. The discharge power of the DBDs operating in different working gases can be obtained from voltage-versus-charge plots or so-called Lissajous figures [25,27].…”
Section: Methodsmentioning
confidence: 98%
“…These microdischarges are of nanosecond duration and are randomly distributed over the dielectric surface [24][25][26][27]. With respect to a uniform surface treatment, a homogeneous discharge condition is very desirable and it has been demonstrated that a homogeneous DBD can be obtained under special, quite restrictive conditions [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Under (very) special conditions of the operation, there exist a diffuse (glow) mode, too. In the latter case, referred to as atmospheric pressure glow discharge (APGD), the BDs are very suitable for a uniform surface treatment [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%